Risks Identification In Bantengan Arts Activities As A Basis For Community Service Activities Based On Occupational Safety And Health (K3): Identifikasi Resiko Aktifitas Kesenian Bantengan Sebagai Dasar Kegiatan Pengabdian Masyarakat Berbasis Keselamatan Dan Kesehatan Kerja (K3) - Qomariyatus Sholihah; Endra Yuafanedi Arifianto; Puji Setyaningsih (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
The Bantengan art form in Malang, East Java, is a performing art form generally performed in open spaces, often with bamboo fences separating the audience. This traditional dance is characterized by energetic and dynamic physical movements. It is important to provide the public with information and knowledge about the risks of injury. This situation has the potential to cause injury to both performers and spectators. This article aims to identify the risks of Bantengan art activities as a basis for community service activities based on occupational safety and health (K3) aspects. The identification was conducted on Bantengan performances held in Cemorokandang Village, Kedungkandang District, Malang City. Observations and documentation were conducted of the performance area and the activities of the Bantengan performers. The observations revealed several potential hazards that pose a risk to occupational safety and health.